Efficacy of nab-paclitaxel does not seem to be associated with SPARC expression in metastatic breast cancer - Schneeweiss, Andreas; Seitz, Julia; Smetanay, Katharina; Schütz, Florian; Jäger, Dirk; Zorn, Markus; Sinn, Peter; Marmé, Frederik (Anticancer research, 2014)
Aim: To evaluate the predictive value of the expression of the secreted protein acidic and rich in cysteine (SPARC) for nab-paclitaxel in metastatic breast cancer (MBC). Patients and Methods: Forty-four patients with progressive MBC were prospectively treated with nab-paclitaxel. Expression of SPARC in tumor cells was assessed by an immunoreactive score, integrating staining intensity and percentage of positive tumor cells; expression in stroma based on staining intensity. SPARC serum levels were determined before 1st and 2nd cycle of nab-paclitaxel and at progression. By applying several cut-offs the association between SPARC expression or serum levels and clinical end-points was analyzed. Results: No clear association between expression of SPARC in primary or metastatic tumor tissue or in serum and any clinical end-point could be detected regardless of the various cut-offs applied. Conclusion: Efficacy of nab-paclitaxel in MBC does not seem to be associated with expression of SPARC in tumor tissues or serum.